Characteristic of microcirculatory changes in patients with primary Raynod's phenomenon by videocapillaroscopy - T A Nevskaya; N G Guseva (Научно-практическая ревматология)
Objective. To study prevalence and structure of videocapillaroscopic findings in primary Raynaud's phenomenon (PRP) and their relation to clinical picture. Methods. 20 pts with PRP and 15 controls were examined by videocapillaroscopy. Results. The presence of homogenous enlarged (mean loop diameter 33,6±7,7 m, p<0,0005) and elongated (mean loop length 301±109 m, p<0,0005) capillaries, multiple punctate hemorrhages or confluent areas of hemorrhage was characteristic of PRP group. Nonspecific capillary changes often found in PRP consisted of tortuous venular part (50%), bushy capillaries (20%). isolated punctate hemorrhages (19%), increased visibility of subpapillary venous plexus (20%). The prevalence of cyanosis in clinical picture of PRP was accompanied by considerable enlargement of venular parts of the loops, prominence of subpapillary vessels, minor dystrophies (tortuous, bushy capillaries) were more frequently seen in pts with longer disease duration. Conclusion. PRP is characterized by structural capillary changes which must be taken into consideration in diagnosis and differential diagnosis of primary and secondary Raynaud's phenomenon.